HOW SMART ARE YOU? - Sultonova Dildora Sherzod qizi (Ustozlar uchun, 2025)
Abstract:This paper explores the multifaceted nature of intelligence from psychological, educational, and technological perspectives. It discusses traditional and contemporary models of intelligence, including emotional and artificial intelligence. The article also addresses cultural perceptions of intelligence and the impact of modern technologies on human cognitive skills.